Atypical cytological changes mimicking SIL of the uterine cervix in allogenic hematopoietic stem cell transplantation recipients treated with busulfan. Issue 6 (30th May 2019) - Saco, Adela; Alòs, Silvia; Esteve, Roser; Suárez‐Lledó, María; Martínez, Carmen; Perez, Francisco M.; Vega, Naiara; Martí, Cristina; Torne, Aureli; Ordi, Jaume; del Pino, Marta
Abstract : Background: Allogenic hematopoietic stem cell transplantation (allo‐HSCT) is a common procedure in hematological disorders and is preceded by a conditioning regimen that usually includes busulfan. The immunosuppression caused by the conditioning regimen and graft‐versus‐host disease prophylaxis is associated with human papillomavirus (HPV) persistence and, consequently, with an increased risk of cervical cancer (CC) and squamous intraepithelial lesions (SILs)—the precursors of CC. A gynecological check‐up that includes CC screening is recommended in these patients. Methods: All female recipients of allo‐HSCT undergo routine gynecological check‐up that includes CC screening. Cervical samples were obtained for liquid‐based cytology and HPV testing. Cytology smears were stained with the Papanicolaou (Pap) technique. A colposcopy evaluation was performed if any abnormal result in the screening tests was obtained. Results: Among 15 women undergoing gynecological examination at 1 year after allo‐HSCT who had received a conditioning regimen that included busulfan, 4 (26.7%) showed atypical squamous cells in the Pap smear, suggesting high‐grade SIL. The abnormalities were identified from 136 to 271 days after allo‐HSCT. In all cases, HPV testing was negative, and colposcopy examination was normal. The cytological abnormalities regressed in 3 of the women after 1 year but persisted in 1 woman at day 382 after allo‐HSCT. Conclusions: Treatment‐related atypia mimicking SIL is a common finding in allo‐HSCT recipients who have received busulfan, particularly in the first year after the procedure. However, atypical changes may persist for more than 1 year. Clinical information, HPV testing, and colposcopy examination are critical to prevent misdiagnosis and overtreatment in these patients. Abstract : Treatment‐related atypia mimicking premalignant lesions in the uterine cervix is a common finding in allogenic hematopoietic stem cell transplantation recipients who have received busulfan. Clinical information, human papillomavirus testing, and colposcopy examination are critical to prevent misdiagnosis and overtreatment in these patients.